Flying At Night : Poems 1965-1985 - Kooser, Ted (Book collections on Project MUSE., 2005)
Named U.S. Poet Laureate for 2004-2006, Ted Kooser is one of America's masters of the short metaphorical poem. Dana Gioia has remarked that Kooser has written more perfect poems than any poet of his generation. In Flying at Night: Poems 1965-1985, Kooser has selected poems from two of his earlier works, Sure Signs and One World at a Time (1985). Taken together or read one at a time, these poems clearly show why William Cole, writing in the Saturday Review, called Ted Kooser ""a wonderful poet, "" and why Peter Stitt, writing in the Georgia Review, proclaimed him ""a skilled and cunning writer